The Psychology of Tsismis: A Phenomenological Study About Housewives’ Gossip Engagement - Suing, Nissi; Gorospe, Junelie; Labto, Lawrence; Pinca, Junea Paula; Tomas, Rodrigo (Journal of Interdisciplinary Perspectives, 2024)
The act of gossiping, or "pakikipagtsismisan," is often observed in Filipino culture and pervasive throughout its society. This study explores the psychology of "tsismis" through the perspectives of housewives in selected areas of the National Capital Region (NCR) of the Philippines. Its aim is to investigate the phenomenon of "pakikipagtsismisan" within the Filipino community, particularly among housewives. The study also seeks to understand the motivations of participants for engaging in this activity, as well as the potential advantages and disadvantages they derive from it. A qualitative research design, specifically a phenomenological approach, was employed to explore this phenomenon. Semi-structured interviews were conducted with 11 participants until saturation was reached. Thematic analysis was used to analyze the gathered data, revealing several themes that addressed the research questions posed by the study. "Tsismis" was found to be deeply ingrained in Filipino culture for these housewives, serving various purposes for them individually. Some participants viewed it as a form of entertainment, a source of information, a means of connecting with others, and even as a defense mechanism. Additionally, the results indicated that "tsismis" significantly impacts the well-being of these housewives.